A simplified constitutive model for a SEBS gel muscle simulant - Development and experimental validation for finite elements simulations of handgun and rifle ballistic impacts - Riccardo Andreotti; Valentina Leggeri; Andrea Casaroli; Mauro Quercia; Cristian Bettin; Mauro Zanella; Marco V. Boniardi (Fracture and Structural Integrity)
An original simplified constitutive model is proposed to simulate the effects of ballistic impacts on blocks of synthetic muscle simulant based on mineral oil and styrene ethylene-butylene styrene polymers (SEBS) as a convenient substitute for Fackler ballistic gelatin. The model is based on a quasi-static elastic-plastic model associated with hydrodynamic properties regulated by a polynomial equation of state. The paper illustrates the development and experimental validation of the model to simulate 9x21mm full metal jacket (FMJ) round-nose, 7.62x39 mm FMJ and 5.56x45 mm NATO bullets penetrating 145x145x400 mm gel blocks. All material parameters are provided to be implemented in built-in LS-Dyna keywords. The validation confirms the effectiveness of the model and suggests possible further developments. The work also confirms the tested synthetic gel as a valid and convenient substitute for Fackler 10% ballistic gelatin at 4 C